1998
DOI: 10.1023/a:1018867209170
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Platelet-derived growth factors (PDGF) are mitogenic polypeptides that are involved in cellular proliferation and tissue repair. The expression of PDGFs and type beta PDGF receptor was examined in the normal human pancreas and in chronic pancreatitis, a fibrotic disease associated with fibroblastic proliferation, atrophy, and acinar cell dedifferentiation. In the normal human pancreas, PDGF A chain mRNA levels were relatively abundant, whereas PDGF B chain mRNA levels were not detected, and type beta PDGF rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Currently, numerous in vivo and in vitro studies have provided strong evidence for a pivotal role for pancreatic stellate cells (PSCs) in fibrogenesis associated with acute and chronic pancreatitis [8][11]. In addition to the elimination of the conditions inducing acinar cell injury (e.g., alcohol) and the reduction of the inflammatory response of the host, therapeutic targeting of PSCs may represent a promising new strategy for reducing fibrogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, numerous in vivo and in vitro studies have provided strong evidence for a pivotal role for pancreatic stellate cells (PSCs) in fibrogenesis associated with acute and chronic pancreatitis [8][11]. In addition to the elimination of the conditions inducing acinar cell injury (e.g., alcohol) and the reduction of the inflammatory response of the host, therapeutic targeting of PSCs may represent a promising new strategy for reducing fibrogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and clinical investigations of HGF have revealed that aberrant HGF/Met signaling contribute to the tumorigenesis of various neoplasms such as sarcomas (Rong et al, 1993;Maier et al, 1996), carcinomas (Ebert et al, 1994), gliomas (Rosen et al, 1996) and leukemias (Hino et al, 1996). For example, coexpression of human Met and HGF caused normal cell lines such as NIH3T3 ®broblasts and C127 cells to become tumorigenic in nude mice and acquire an invasive and metastatic phenotype (Tsarfaty et al, 1994;Rong et al, 1994;Je ers et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…PDGF-β represents the most potent mitogen for PSCs, both PDGF-β and the PDGF-β receptor have been shown to be over expressed in human CP 18 . However, we are unaware of any studies that investigated the role of the PDGF-β variants in CP.…”
Section: Discussionmentioning
confidence: 99%